La Política Tributaria del Impuesto a la salida de Divisas (ISD), estimula el Empleo y la Producción o Ahuyenta la Inversión Extranjera y la Creación de Fuentes de Trabajo - Salinas Zhigui, Ismael (2017)
In this paper an approach Tax Remittance, and major tax reforms are made, allowing us to know how this tax has evolved since its inceptionto the present. The tax on foreign exchange outflows (ISD), was created in 2008, with the aim of regulating the outflow of capital of Ecuador, so it can be shown that by increasing the tax on foreign exchange outflows purpose to increase tax collection, attentive to the constitutional principles of taxation, the policy of promoting and encouraging the use and production of goods and services, driving away foreign investment and affecting the creation of jobs. The changes made to the tax seek to control the outflow of capital abroad, prevent tax evasion, affecting the country's economy. At the same time as the implementation of this tax affect on foreign investment and impact it had on more expensive imports and as several products. Which I have set targets, make a theoretical, normative study of tax outflow of foreign exchange, to show that this tax, attentive to the constitutional principles of taxation, creating jobs and scares away foreign investment. With the creation of the Tax Remittance, a tax rate, the operative event and transactions that are exempt from tax it is included. Both Importer sector and the financial sector must undergo the Tax Remittance and this applies as 5 indicated in the law .The Tax Output Currency (ISD) which was created on the value of all operations and transactions monetary carried out abroad, with or without the involvement of financial institutions. Through the method of analysis and comparative method it was found that by increasing the tax on foreign exchange outflows, a direct effect occurs with foreign capital, as it limits investment and not enter our country, so costly for investors pull their capital, which have preferred to neighboring countries without this tax, causing more migration of people because there is no jobs.